2012
DOI: 10.1007/s00011-012-0487-x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori promotes apoptosis, activates cyclooxygenase (COX)-2 and inhibits heat shock protein HSP70 in gastric cancer epithelial cells

Abstract: ObjectiveApoptosis plays an important role in the regulation of gastric epithelial cell number and gastrointestinal disorders induced by Helicobacter pylori (Hp). Heat shock proteins (HSPs) are involved in cell integrity, cell growth and in gastric mucosa colonized by Hp. COX-2 was implicated in Hp-induced carcinogenesis but the effects of this germ and CagA cytotoxin on HSP70, COX-2, Bax and Bcl-2 in gastric cancer epithelial cells have been little studied.Material and methodsWe determined the expression for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Tumorigenic pathogens or persistent infections are able to boost the host immunity and cause continuous inflammation to initiate carcinogenesis. For instance, it was considered that persistent Helicobacter pylori infection was associated with the pathogenesis of gastric cancer and mucosa-associated lymphoid tissue lymphoma [57], hepatitis B or C viruses with hepatocellular carcinoma, or Schistosoma or Bacteroides species with bladder and colon cancer, respectively [58]. Consistent inflammation can induce the occurrence of autoimmunity, oncogenic mutations, genomic instability, early tumor promotion, or angiogenesis.…”
Section: Roles Of Chemokines In Cancer-related Inflammationmentioning
confidence: 99%
“…Tumorigenic pathogens or persistent infections are able to boost the host immunity and cause continuous inflammation to initiate carcinogenesis. For instance, it was considered that persistent Helicobacter pylori infection was associated with the pathogenesis of gastric cancer and mucosa-associated lymphoid tissue lymphoma [57], hepatitis B or C viruses with hepatocellular carcinoma, or Schistosoma or Bacteroides species with bladder and colon cancer, respectively [58]. Consistent inflammation can induce the occurrence of autoimmunity, oncogenic mutations, genomic instability, early tumor promotion, or angiogenesis.…”
Section: Roles Of Chemokines In Cancer-related Inflammationmentioning
confidence: 99%
“…This is accompanied by a shift towards a proapoptotic homeostasis with increased expression of bax and decreased expression of bcl2 [199,200]. The induction of oncogenes like cmyc is also interfering with these processes [199,201].…”
Section: Response To H Pylori In the Gastric Mucosamentioning
confidence: 99%
“…5,[32][33][34][35][36][37][38] The specific presentation depends on the virulence features of the bacteria, host characteristics and environmental factors. Many studies have shown that the most virulent genotypes of H. pylori are cagA(+), vacA (+).…”
Section: Clinical Presentationmentioning
confidence: 99%